Distal Humerus Morphological Analysis of Chinese Individuals: A Statistical Shape Modeling Approach. Issue 10 (14th September 2022) - Zhao, Wei; Guo, Yao; Xu, Chuangye; Pei, Guoxian; Basnet, Shiva; Pei, Yanjun; Su, Xiuyun
Abstract : Objective: A detailed analysis of the morphology of distal humeral articulation can help in the creation of anatomic prostheses of hemiarthroplasty. This study used statistical shape modeling to evaluate the 3D morphology of the distal humerus in healthy Chinese individuals and to investigate the proper articular morphology differences. Methods: A statistical shape model (SSM) of the distal humerus was created using CT scans of 106 survey‐confirmed nonpathologic elbows. In addition, the articular components of each principal component (PC) were selected and fitted on the mean mode. The Euclidean point‐to‐mesh distance of articular modes was calculated as a measurement the proper change in the morphology of the articulation. Results: The first seven PCs jointly accounted for 80.9% of the total variation (44.4%, 12.2%, 7.9%, 5.9%, 4.1%, 3.4% and 3%, respectively). In the mean model, the distance between the medial and lateral epicondyles was 57.4 mm, the width of the articulation was 42.1 mm, and the angle of the transepicondylar line (TEL) and C line was 4.8°. The articular surface differences of the first PC were significant (RMS: 1.43 mm in the −3 SD model and 2.38 mm in the +3 SD model), whereas under other conditions, the differences were not remarkable despite the maximum deformation not exceeding 1 mm. Conclusion: A novel method (SSM) was used to evaluate the 3D morphology of the distal humerus in healthy Chinese individuals and investigate the proper articular shape differences. We found the proper shape of articular surface basically transformed into one variation pattern which was relevant to the bone size, even though the morphology of distal humerus possessed complicated variation modes. The findings of this study can be helpful to design the next generation of elbow hemiarthroplasty in the future. Abstract : Through a statistical shape model (SSM) we found although the distal humeral morphology possessed complex variation modes, the proper shape of the articular surface primarily transformed into one variation pattern. The database we used reflects the population‐specific characteristics of the bony structures, which can be useful in the development of distal humeral hemiarthroplasty implants.